A Portrait of Using Direct Method in Speaking Instruction By the English Teacher of Islamic Junior High School In Lumajang: A Descriptive Study - Rizky Nur Arifatul Fauziyyah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
In Indonesia, English is taught as a foreign language in schools, but students have limited opportunities to practice speaking outside the classroom. This results in minimal speaking time and restricted language input. Mukminatien (1995) suggests that teachers should provide more input in class and encourage students to use English beyond the classroom. To address this issue, teachers can select effective teaching strategies, such as the Direct Method, which is considered a suitable approach for developing speaking skills.
Repo 2 Juli 2026_ Rudy k Validasi dan Finalisasi Ratna 2 Juli 2026
Keywords: A Portrait of Using Direct Method